A study on an extraction gelatin from Tuna eye’s (thunnus sp.) - Sandria, Nofri; Sukmiwati, Mery; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted to evaluate the effect of different HCl concentrations on gelatin properties extrated from tuna eye’s. About 13 kg tuna eye’s were taken from PT. Dempo Andalas Samudera, West Sumatera. Tuna eye’s was diveded into 3 groups and each group was extracted for its gelatin using HCl solution at different concentrations (4%, 5% and 6%). The extracted gelatins were evaluated for yield, pH, proximate composition and isoelektric point. The yield and pH of the gelatin were 0,28%-0,71% and 3,11-3,89 respectively. The yield and pH of the gelatin increased as the increasing of HCl concentration; and the yield and pH of the gelatin extracted using 4% HCl resulted in the best quality product. Protein, fat, moisture, ash and isoelektric point of the best gelatin were 85,76%; 4,76%; 1,87%; 5,06%; pH 7,5 respectively.Keyword: Gelatin, eye’s tuna, HCl Solution.